PENGARUH CAPITAL ADEQUACY DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN ON ASSET: STUDI PADA BANK BPR DI INDONESIA - Sri Suriyani; Grahita Chandrarin; Junianto Tjahyo Darsono (Jurnal Ilmu Ekonomi dan Bisnis, 2019)
Profitability is bank performance indicator that effort in certain time. Profitability is known by Return On Asset (ROA). Return On Asset (ROA) is influenced by Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR). To improve the influence Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) need the research. This research uses quantitative method. The population is all the BPR in Indonesia. The population are consist of 100 BPR. Technique of sampling is used census. This research sample is 100 BPR. The data collection technique is questioner. Data is analyzed by linear regression.The results of this research shows that Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) have influence significantly to the Return On Asset (ROA). Capital Adequacy Ratio (CAR) has not influence significantly to the Return On Asset (ROA). Loan to Deposit Ratio (LDR) have influence significantly to the Return On Asset (ROA).Loan to Deposit Ratio (LDR) is more dominant variable than Capital Adequacy Ratio (CAR) influences Return On Asset (ROA). So may the bank need to improve the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) because these variables have influence significantly to Return On Asset (ROA).